2010
DOI: 10.1007/s00467-009-1331-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of tacrolimus in stable paediatric renal transplant recipients

Abstract: Because tacrolimus (Tac) has a narrow therapeutic index and highly inter- and intra-individual variable pharmacokinetic (PK) characteristics, monitoring of drug exposure is recommended, but limited data are available on the kinetics of Tac in paediatric renal transplant recipients, especially of limited sampling strategies. To investigate the correlation between Tac trough level (TL) and the 0-12 h area under the curve (AUC), and the value of abbreviated AUC monitoring, we evaluated 12 h PK profiles in 27 chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…Our results demonstrated that the correlation coefficients (r 2 ) between C 0h and AUC were moderate, in both the original dataset and the dataset used for external validation. This is in agreement with the previous reports on kidney-transplanted children showing that correlation coefficients (r 2 ) may vary widely, between 0.30 and 0.79, 10,11,[18][19][20][21][22] suggesting that C 0h only is not a good surrogate marker of tacrolimus AUC, despite its widespread use for monitoring tacrolimus treatment, 1 AUCbased dosage individuation remains the gold standard 8 for dosage adaptation as it was effective in optimizing efficacy and reducing both rejection or toxicity. 8 The LSS approach facilitates dosage adaptation in clinical practice by providing an ethical, cost-and timeeffective method to monitor tacrolimus.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results demonstrated that the correlation coefficients (r 2 ) between C 0h and AUC were moderate, in both the original dataset and the dataset used for external validation. This is in agreement with the previous reports on kidney-transplanted children showing that correlation coefficients (r 2 ) may vary widely, between 0.30 and 0.79, 10,11,[18][19][20][21][22] suggesting that C 0h only is not a good surrogate marker of tacrolimus AUC, despite its widespread use for monitoring tacrolimus treatment, 1 AUCbased dosage individuation remains the gold standard 8 for dosage adaptation as it was effective in optimizing efficacy and reducing both rejection or toxicity. 8 The LSS approach facilitates dosage adaptation in clinical practice by providing an ethical, cost-and timeeffective method to monitor tacrolimus.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, LSS approach for tacrolimus has been widely developed in adult organ transplant patients 9,23 but not in children. Only 2 LSS using multiple regression analysis have been published, 10,11 and their application remains difficult in clinical practice, as up to 4 samples are collected up to 6 hours postdose, and there is no external validation. In our current investigation, we focused on the development and validation of clinically reliable LSS for estimating AUC in pediatric patients, with samples limited to 3, collected within 3 hours of drug administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies found that C 0 could not reflect the inter-individual difference of total TAC exposure reliably. Poor correlation between the TAC C 0 and AUC 0-12 was found in kidney [8,9] and liver [10,11] transplant patients.…”
Section: Introductionmentioning
confidence: 99%
“…Results: Twenty-eight models including 1, 2, 3 and 4 blood time points sampling were established (r 2 = 0.653-0.979). The best model for prediction of TAC AUC 0-12 was 0.81 + 1.73C 1 + 1.32C 2 + 3.87C 4 + 3.75C 8 (r 2 = 0.979). Forty profiles (85.1%) had estimated TAC AUC 0-12 within ±15% of observed TAC AUC 0-12 .…”
mentioning
confidence: 99%